Karakteristik Penyakit ISK Pada Ibu Hamil Literature Review - Dwidamayanti, Vellya; Ananda, Fadli; Lauwrenz, Happy (Universitas Pahlawan Tuanku Tambusai, 2024)
Urinary tract infection, or UTI, is one of the most common infectious diseases worldwide and a leading cause of illness and death worldwide, especially in less developed countries. When there are many bacteria in the urine, they can infect the urinary system and cause a clinical condition called UTI. A higher incidence of urinary retention is associated with mechanical and hormonal changes that occur during pregnancy. We hope to learn more about the causes of UTI in pregnant women by conducting this study. A literature review following the PRISMA approach was used. Journal articles and other scientific publications were retrieved from PubMed, Garuda Portal, and Google Scholar according to SINTA IV and V criteria for 2020-2023. This search resulted in 826 articles using the keywords UTI and pregnant women. The screening process began with the selection of 15 research publications according to the inclusion criteria. The features of UTI in pregnant women were reported in fifteen papers screened from this literature review. The results showed that the likelihood of urinary tract infection (UTI) during pregnancy was correlated with demographic variables including education level, occupation, gestational age, and use of urinary restraints.